Gut microbiota mediated T cells regulation and autoimmune diseases - Bhutta, Nabeel Khalid; Xu, Xiujin; Jian, Cuiqin; Wang, Yifan; Liu, Yi; Sun, Jinlyu; Han, Bingnan; Wu, Shandong; Javeed, Ansar (Frontiers in Microbiology, 2024)
Gut microbiota regulates the immune system, the development and progression of autoimmune diseases (AIDs) and overall health. Recent studies have played a crucial part in understanding the specific role of different gut bacterial strains and their metabolites in different AIDs. Microbial signatures in AIDs are revealed by advanced sequencing and metabolomics studies. Microbes such as Faecalibacterium prausnitzii, Akkermansia muciniphila, Anaerostipes caccae, Bacteroides sp., Roseburia sp., Blautia sp., Blautia faecis, Clostridium lavalense, Christensenellaceae sp., Coprococcus sp., Firmicutes sp., Ruminococcaceae sp., Lachnospiraceae sp., Megamonas sp., Monoglobus sp., Streptococcus pneumoniae and Bifidobacterium sp. help maintain immune homeostasis; whereas, Prevotella copri, Ruminococcus gnavus, Lactobacillus salivarius, Enterococcus gallinarum, Elizabeth menigoseptica, Collinsella sp., Escherichia sp., Fusobacterium sp., Enterobacter ludwigii, Enterobacteriaceae sp., Proteobacteria, Porphyromonas gingivalis, Porphyromonas nigrescens, Dorea sp., and Clostridium sp. cause immuno-pathogenesis. A complex web of interactions is revealed by understanding the influence of gut microbiota on immune cells and various T cell subsets such as CD4+ T cells, CD8+ T cells, natural killer T cells, γδ T cells, etc. Certain AIDs, including rheumatoid arthritis, diabetes mellitus, atopic asthma, inflammatory bowel disease and non-alcoholic fatty liver disease exhibit a state of dysbiosis, characterized by alterations in microbial diversity and relative abundance of specific taxa. This review summarizes recent developments in understanding the role of certain microbiota composition in specific AIDs, and the factors affecting specific regulatory T cells through certain microbial metabolites and also focuses the potential application and therapeutic significance of gut microbiota-based interventions as novel adjunctive therapies for AIDs. Further research to determine the precise association of each gut bacterial strain in specific diseases is required.